Multi-successive-step pH sensitive procedure: Survey of dominant formation mechanism of therapeutic SPIONs. Issue 5 (1st April 2019) - Ghazanfari, Mohammad Reza; Shams, S. Fatemeh; Jaafari, Mahmoud Reza; Kashefi, Mehrdad
Abstract: In the present study, multistep formation mechanism and synthesis reaction pathway of therapeutic magnetite nanoplatforms during a modified chemical coprecipitation method were identified. Critical reaction steps were considered through the study of pH variation trend as a function of structural, microstructural, and magnetic properties. Structural, microstructural, and magnetic characteristics were investigated using XRD, FT-IR, DLS, TEM, and VSM techniques. Results demonstrate the synthesis pathway of magnetite nanoparticles significantly depends on reaction pH and could be deduced in four successive transformation steps as follows: (I) initial materials to ferrous hydroxide, (II) ferrous hydroxide to lepidocrocite phase, (III) lepidocrocite to goethite phase, and (IV) goethite to magnetite (or/and maghemite) phase. Moreover, aqueous ferrofluids of synthesized Fe3 O4 nanoparticles demonstrate significant heat-generation ability and SAR values upon applying AC magnetic field which confirm their appropriate efficiency to utilize for therapeutic hyperthermia applications.